Metas de inflação, câmbio flexível e autonomia de política monetária - Joao Luis Resende (2006)
The purpose of this study is investigate the loss or gain of autonomy of monetary policy resulted of inflation targeting regime adoption together with floating exchange rate system in developed and emerging countries. In order to accomplish this, carry out analysis of pulse-response function and variance decomposition originated of vector auto-regressions estimations. The empiric results suggest that inflation targeting adoption leaded to: i) in case of development countries, loss of autonomy of monetary policy in Chile and undefined results in Brazil and Mexico and; ii) gain of autonomy of monetary policy for analysed developed countries. The main conclusion is the divergent behavior of monetary policy autonomy in developed and emerging countries when the inflation targeting was adopted together with floating exchange rate system.